A computational analysis of the impact of bore-to-stroke ratio on emissions and efficiency of a HSDI engine. (1st November 2017) - Benajes, J.; Novella, R.; Pastor, J.M.; Hernández-López, A.; Duverger, T.
Highlights: A CFD study of the impact of bore-to-stroke on engine performance has been done. Efficiency increases with smaller B/S ratio due to lower heat losses. Higher NOx emissions for lower B/S ratio mainly due to faster mixing and combustion. Lower B/S ratio decreases fuel rich pockets in squish region and then soot formation. Abstract: Research on combustion systems for Internal Combustion Engines (ICE) is guided by the necessity of improving engine efficiency while achieving the pollutant regulations. In this framework, this study identifies and describes the effect of the bore-to-stroke ratio (B/S) on the combustion system performance and emissions by means of computational fluid dynamics (CFD). The study is applied to a 4-cylinder 4-stroke High Speed Direct Injection (HSDI) CI engine. It is divided in two parts, the first part is focused on one operating point and presents a detailed description of the main effects of different B/S ratios configurations, and the second part compares the results with different engine operating conditions. For both parts the air management, injection settings and compression ratio were kept constant in order to isolate the impact of the B/S ratio. The results confirmed that the indicated thermal efficiency was increased for lower B/S ratio because of the combustion chamber surface area decrease and faster combustion. Regarding the emissions, NOx and soot presented a strong and opposed dependence on B/S ratio generated mostly due to enhanced air–fuel mixing for lower B/S ratio. Finally, those trends were proven to be independent from the operating condition, giving the study a more general value.